Development of PBL-Based E-LKPD to Improve Students’ Learning Motivation and Critical Thinking Skills - Mawar Melinah; Syarif Fitriyanto; Suji Ardianti; Sri Nurul Walidain; Romi Aprianto; Fahmi Yahya; Hermansyah Hermansyah (Indonesian Publication Center, 2026)
This study was motivated by the fact that students demonstrated suboptimal learning motivation and weak critical thinking skills in understanding the abstract topic of temperature and heat. The objective of this research was to develop a physics E-LKPD based on the Problem-Based Learning (PBL) model and to examine its validity, practicality, and effectiveness in learning activities. The study employed a Research and Development (R&D) approach guided by the ADDIE framework, consisting of five main stages: analysis, design, development, implementation, and evaluation. The participants included one physics teacher and 35 eleventh-grade students from MAN 1 Sumbawa. Data were collected through expert reviews, surveys from both the teacher and students, as well as pre- and post-tests to assess students’ motivation levels and critical thinking abilities. The findings revealed that the developed E-LKPD achieved a validity score of 90.4%, a practicality score of 88%, and an effectiveness level reflected by an average N-Gain value of 0.71, which falls into the high category. Furthermore, students’ learning motivation reached 82.44% (high category), and their critical thinking ability reached 79.3% (moderately high). Therefore, the E-LKPD, designed with a Problem-Based Learning (PBL) approach, is considered suitable as a physics learning medium, capable of enhancing both the quality of the learning process and students’ learning outcomes.